2021
DOI: 10.1007/s00404-021-06145-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of preoperative cone biopsy with recurrences after radical hysterectomy

Abstract: Objective To evaluate association of preoperative cone biopsy with the probability of recurrent disease after radical hysterectomy for cervical cancer. Methods This is a retrospective single-center study. Patients with cervical cancer stage IA1 with LVSI to IIA2 and squamous, adenosquamous and adenocarcinoma subtype were included. Patients were analyzed for general characteristics and recurrence-free survival (RFS). Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…The reasons were that a uterine manipulator was used, information on the use of uterine manipulator was lacking, patients who received neoadjuvant therapy or advanced stages of cervical cancer were involved. Finally, six studies were included in the meta‐analysis 19–24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons were that a uterine manipulator was used, information on the use of uterine manipulator was lacking, patients who received neoadjuvant therapy or advanced stages of cervical cancer were involved. Finally, six studies were included in the meta‐analysis 19–24 …”
Section: Resultsmentioning
confidence: 99%
“…Detailed characteristics of the included studies are presented in Table 1. Studies were published between 2019 and 2022, with one study each conducted in Sweden, 19 Germany 22 and Norway, 23 two studies conducted in Japan 21,24 and one study jointly conducted in Europe 20 . None of the six studies had an randomised controlled trial (RCT) design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contradictory results of various studies lead to the hypothesis that reduced survival after MIS might depend on failure to prevent tumor cell contamination through the use of uterine manipulators, intracorporal colpotomy or lack of vaginal cuff closure [10][11][12][13]. Recent studies showed that patients who underwent preoperative conization appear to have excellent survival even after laparoscopic surgery [14][15][16][17][18][19]. However, the enrolled population in these studies was based on the preoperative diagnosis with confounding factors such as larger tumor size, lymph node metastasis, and different surgical approach.…”
Section: Introductionmentioning
confidence: 99%